Nanosilica and Polyacrylate/Nanosilica: A Comparative Study of Acute Toxicity. (15th February 2016) - Niu, Ying-Mei; Zhu, Xiao-Li; Chang, Bing; Tong, Zhao-Hui; Cao, Wen; Qiao, Pei-Huan; Zhang, Lin-Yuan; Zhao, Jing; Song, Yu-Guo
Abstract : We compared the acute toxicity of nanosilica and polyacrylate/nanosilica instillation in Wistar rats (n = 60 ). Exposure to nanosilica and polyacrylate/nanosilica showed a 30% mortality rate. When compared with saline-treated rats, animals in both exposure groups exhibited a significant reduction of PO2 (P < 0.05 ) at both 24 and 72 hr. after exposure. Both exposure groups exhibited a significant reduction of neutrophils in arterial blood compared to saline controls (P < 0.05 ) 24 hr. after exposure. The levels of blood ALT and LDH in exposed groups were found to be significantly increased (P < 0.05 ) 24 hr. following exposure. The exposed groups exhibited various degrees of pleural effusion and pericardial effusion. Our findings indicated respiratory exposure to polyacrylate/nanosilica and nanosilica is likely to cause multiple organ toxicity.